Focal fatty sparing as an indicator of higher-grade fatty liver assessed by attenuation imaging: a prospective clinical study in NAFLD population - Miller, Elisabeth; Schmidberger, Julian; Kratzer, Wolfgang (Zeitschrift für Gastroenterologie, 2021)
Background As part of a prospective clinical study, the degree of hepatic fatty degeneration was quantified in a patient population with nonalcoholic fatty liver disease and sonographically diagnosed with hepatic steatosis using attenuation imaging.Methods A total of 113 patients with hepatic steatosis were examined, of whom 35 showed focal fatty sparing. Patients with the condition after right nephrectomy, other known liver diseases, and relevant alcohol consumption were excluded from the evaluation. B-scan sonography and sonographic quantification of steatosis content using attenuation imaging (Aplio i800 Canon Medical Systems) were performed. Attenuation imaging is a new ultrasound-based measurement technique that allows objective detection and quantification of hepatic steatosis.Results The prevalence of focal fatty sparing was 31.0% in the patient population examined. Patients with focal fatty sparing showed a statistically significantly higher attenuation coefficient in contrast to patients without focal fatty sparing (0.79 ± 0.10 vs. 0.66 ± 0.09 dB/cm/MHz, p < 0.0001).Conclusion Detection of focal fatty sparing is associated with an increased attenuation coefficient and is thus an expression of higher-grade hepatic fatty degeneration. Patients with focal fatty sparing are more often male and have a higher BMI and a larger liver than patients with nonalcoholic fatty liver disease without focal fatty sparing.
Keywords: Schallwellenattenuation; Fokale Minderverfettung; Fettlebererkrankung; Leber